Life insurance convexity - Nicolaus Grochola; Helmut Gründl; Christian Kubitza (European Central Bank (ECB), 2023)
Life insurers sell savings contracts with surrender options, which allow policyholders to prematurely receive guaranteed surrender values. These surrender options move toward the money when interest rates rise. Hence, higher interest rates raise surrender rates, as we document empirically by exploiting plausibly exogenous variation in monetary policy. Using a calibrated model, we then estimate that surrender options would force insurers to sell up to 2% of their investments during an enduring interest rate rise of 25 bps per year. We show that these fire sales are fueled by surrender value guarantees and insurers' long-term investments.
Keywords: G22; E44; E52; G52; 330; Life Insurance; Liquidity Risk; Interest Rates; Surrender Options; Systemic Risk